Solid waste material-based microcrystalline foamed ceramic material and preparation method thereof

In the preparation process of microcrystalline foam ceramics, the solid waste material-based preparation method is adopted, combined with specific raw material ratios and multi-stage heating and firing technology, the seed crystal, pore stability and porosity in microcrystalline foam ceramics are solved. The problem of high strength and toughness of the material can be achieved and the cost is reduced.

CN119430660APending Publication Date: 2025-02-14SHENYANG JIANZHU UNIVERSITY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411801722.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of seeds, pore stability and porosity in the preparation of microcrystalline foam ceramics.

Method used

The preparation method of solid waste material-based microcrystalline foam ceramic materials, the raw materials include coal gangue, steel slag, glass powder, auxiliary components (such as TiO2, ZrO2), melting components, foaming components and water, through specific mixing and firing Steps, including firing, water quenching, grinding, granulation, pressing, drying and multi-stage heating firing, to improve the strength, toughness and uniformity of the foam ceramics.

Benefits of technology

It significantly improves the toughness and strength of microcrystalline foam ceramics, ensures the uniformity of pore distribution, solves the problem of porosity size, reduces production costs, and reduces dependence on natural mineral resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a solid waste material-based microcrystalline foamed ceramic material and a preparation method thereof, and belongs to the field of building materials, the solid waste material-based microcrystalline foamed ceramic material comprises the following raw materials by weight: 15-32% of coal gangue, 20-38% of steel slag, 30-45% of glass powder, 4-11% of an auxiliary component, 3-7% of a fluxing component, 4-7% of a foaming component, and 1-5% of water; the auxiliary components comprise TiO2 and ZrO2. The preparation method comprises the following steps: uniformly mixing the coal gangue, the steel slag, the glass powder and the auxiliary components, firing, carrying out water quenching, and grinding to obtain a powdery material; uniformly mixing the powdery material, a foaming component, a fluxing component and water, pouring into a mold, standing, demolding and drying to obtain a blank body; and firing the blank according to a specific firing method to obtain the solid waste material-based microcrystalline foamed ceramic material. According to the solid waste material-based microcrystalline foamed ceramic material disclosed by the invention, the bending strength and the toughness are remarkably improved, the situation that the application range is limited due to low strength can be avoided, and the actual use efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a solid waste material-based microcrystalline foam ceramic material and a preparation method thereof. Background Art

[0002] With the development of the times, people's research on foam ceramic technology has become more and more in-depth. The production of microcrystalline foam ceramics is based on the ordinary foam ceramic ingredients, adding a certain amount of nucleating agent to the basic formula, and firing through a certain sintering system. Compared with the low strength, low toughness and high water absorption of ordinary foam ceramics, the strength and toughness of microcrystalline foam ceramics are relatively improved, and the water absorption becomes lower. It is a new type of green material. Due to the huge demand for natural mineral resources in the preparation of microcrystalline glass ceramics, natural resources are in short supply, so we have to turn our attention to waste. The use of waste can not only effectively solve the problem of waste pollution, but also further reduce the production cost.

[0003] As a major country in coal mining, my country produces a large amount of solid waste, coal gangue, in the process of coal mining. The large-scale discharge and accumulation of solid waste not only wastes a lot of land resources, but also seriously damages the local ecological environment. Steel slag is a solid waste discharged in huge quantities during the steelmaking process. It has low activity, poor stability, high hardness, and the processing technology is not yet mature, so its utilization rate is low, which brings a great burden to the environment.

[0004] In my country, building energy consumption is the largest among many energy consumptions. Therefore, using coal gangue and steel slag to produce microcrystalline foam ceramics can not only reduce the pollution of construction industry and industrial waste and improve the ecological environment, but also provide a new type of green building material for people to use.

[0005] In the prior art, Chinese patent authorization CN116969684A discloses a method for preparing microcrystalline ceramics using chrysotile tailings, marble tailings and quartz-containing slag. The three materials are ground and mixed evenly, pressed into shape, and then the formed body is dried, glazed, heat treated and post-treated to finally obtain the finished microcrystalline ceramics.

[0006] Patent authorization CN116655248A discloses a method for preparing microcrystalline ceramics using titanium slag and fly ash as raw materials. The titanium slag and fly ash are ground and mixed evenly, and then granulated with water, and then pressed into shape. Subsequently, the green body is placed in a furnace and heated to 1160-1200°C for sintering. After sintering, the microcrystalline ceramics can be obtained by cooling the furnace.

[0007] However, the above materials cannot solve the problems of the number of seeds, the stability of pores, and the size of porosity in the process of preparing microcrystalline foam ceramics. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a microcrystalline foam ceramic material and a preparation method thereof. The preparation method of the microcrystalline foam ceramic material of the present invention can achieve the purpose of enhancing the strength, toughness and uniform pore distribution of foam ceramics. The microcrystalline foam ceramic material provided by the present invention has high toughness and strength. The technical solution adopted by the present invention is: The first aspect of the present invention provides a solid waste material-based microcrystalline foam ceramic material, wherein the raw materials include, by weight percentage, 15-32% coal gangue, 20-38% steel slag, 30-45% glass powder, 4-11% auxiliary components, 3-7% fluxing components, 4-7% foaming components, and 1-5% water; the auxiliary components include TiO2 and ZrO2.

[0009] Furthermore, among the auxiliary components, the weight ratio of TiO2 and ZrO2 is (1~5):(2~5).

[0010] Preferably, in the auxiliary components, the weight ratio of TiO2 and ZrO2 is 3:2.

[0011] Preferably, the raw materials include, by weight percentage, 16.79% coal gangue, 33.32% steel slag, 30.89% glass powder, 8% auxiliary components, 5% fluxing components, 5% foaming components, and 1% water.

[0012] Furthermore, the coal gangue and steel slag are particles with a particle size not exceeding 0.075 mm obtained by removing impurities, crushing, grinding and screening the coal gangue raw materials and steel slag raw materials respectively.

[0013] Furthermore, the foaming components include SiC, MnO2, and CaCO3 in a weight ratio of (2~5):(0~2):(0~2).

[0014] Preferably, in the foaming components, the weight ratio of SiC, MnO2 and CaCO3 is 3:1:1.

[0015] Furthermore, the fluxing component is borax or fluorite powder.

[0016] Preferably, the weight ratio of the flux component is 5%.

[0017] The second aspect of the present invention provides a method for preparing the above-mentioned solid waste material-based microcrystalline foam ceramic material, comprising the following steps: (1) The coal gangue, steel slag, glass powder and auxiliary components are mixed uniformly, and then fired, water quenched and ground to obtain a powdered material; (2) uniformly mixing the powdered material, foaming component, fluxing component and water, pouring into a mold, letting it stand, demolding, and drying to obtain an embryo body; (3) The embryo body is first heated to 650-900°C at a heating rate of 3-8°C / min and kept warm for 30-50 min, then heated to 800-1000°C at a heating rate of 5-8°C / min and kept warm for 60-80 min, and finally heated to 950-1100°C at a heating rate of 3-8°C / min and kept warm for 60-80 min, to obtain the solid waste material-based microcrystalline foam ceramic material.

[0018] Preferably, the step (3) is to first heat the embryo to 660°C at a heating rate of 5°C / min and keep it warm for 45 minutes, then heat it to 850°C at a heating rate of 6°C / min and keep it warm for 60 minutes, then heat it to 960°C at a heating rate of 6°C / min and keep it warm for 60 minutes.

[0019] The temperature-raising firing method of step (3) above can enable the various raw materials to exert their own advantages, and a nucleation and crystallization reaction occurs during the firing process, so that the prepared sample meets the target requirements and enhances the toughness and strength of the foam ceramic itself.

[0020] Furthermore, the sintering method in step (1) is to increase the temperature to 1200°C~1350°C at a heating rate of 5~30°C / min and keep the temperature for 30~45 min.

[0021] Preferably, the sintering method in step (1) is to increase the temperature to 1350° C. at a heating rate of 15° C. / min and keep the temperature for 40 min.

[0022] Furthermore, the particle size of the powdered material is 150 mesh to 250 mesh.

[0023] It should be noted that the coal gangue and the steel slag are both solid wastes, wherein the coal gangue comes from the non-carbon substances left over from the coal mining process and has a hard texture, and the steel slag comes from the waste materials generated during the steelmaking process.

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a solid waste material-based microcrystalline foam ceramic material and a preparation method thereof. The preparation method of the present invention prepares solid waste material-based microcrystalline foam ceramics on the basis of adding a small amount of nucleating agent, which can reduce a certain amount of production cost.

[0025] (2) Compared with ordinary foam ceramics, the solid waste material-based microcrystalline foam ceramic material prepared by the present invention has greatly improved toughness and strength, which effectively solves the problems of low strength and insufficient toughness of ordinary foam ceramics. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0027] Among the raw materials used in the following examples and comparative examples for preparing the solid waste material-based microcrystalline foam ceramic materials, the coal gangue and steel slag raw materials are from Fushun New Steel Co., Ltd., Liaoning Province, and the chemical compositions are shown in Table 1: Table 1 Chemical composition of raw materials

[0028] The chemical composition of the glass powder includes SiO2 65%-75%, Al2O3 1%-2%, CaO+MgO 10%-20%, Na2O+K2O 10%-20%, and the remaining oxides of iron, titanium, sulfur, etc. are about 0.6%; TiO2 and ZrO2 are purchased from Sinopharm Group and are of analytical grade; borax is purchased from Sinopharm Group and is of analytical grade; SiC, MnO2, and CaCO3 are purchased from Sinopharm Group and are of analytical grade.

[0029] After impurities are removed, sorted and ground, the gangue slag raw materials, waste glass raw materials and steel slag raw materials are sieved with a square hole sieve with an aperture of 0.075 mm to remove particles with a particle size greater than 0.075 mm, thereby obtaining granular gangue, glass powder and steel slag with a particle size not exceeding 0.075 mm.

[0030] The invention provides a solid waste material-based microcrystalline foam ceramic material. The raw materials include, by weight percentage, 15-32% of coal gangue, 20-38% of steel slag, 30-45% of glass powder, 4-11% of auxiliary components, 3-7% of fluxing components, 4-7% of foaming components, and 1-5% of water; the auxiliary components include TiO2 and ZrO2.

[0031] In some examples, the weight ratio of TiO2 and ZrO2 in the auxiliary components is (1~5):(2~5).

[0032] In some examples, the foaming components include SiC, MnO2, and CaCO3 in a weight ratio of (2~5):(0~2):(0~2).

[0033] In some examples, the flux component is borax or fluorite powder.

[0034] The present invention provides a method for preparing solid waste material-based microcrystalline foam ceramics, comprising the following steps: (1) The coal gangue, steel slag, glass powder and auxiliary components are mixed uniformly, and then fired, water quenched and ground to obtain a powdered material; (2) uniformly mixing the powdered material, foaming component, fluxing component and water, pouring into a mold, letting it stand, demolding, and drying to obtain an embryo body; (3) The embryo body is first heated to 650-900°C at a heating rate of 3-8°C / min and kept warm for 30-50 min, then heated to 800-1000°C at a heating rate of 5-8°C / min and kept warm for 60-80 min, and finally heated to 950-1100°C at a heating rate of 3-8°C / min and kept warm for 60-80 min, to obtain the solid waste material-based microcrystalline foam ceramic material.

[0035] In some examples, the firing method in step (1) is to increase the temperature to 1200°C~1350°C at a heating rate of 5~30°C / min, and then keep the temperature for 30~45 min.

[0036] In some examples, the particle size of the powdered material is 150 mesh to 250 mesh.

[0037] The raw materials of Examples 1-5 are shown in Table 2 below, and the remaining ingredient is water.

[0038] Table 2 Raw materials of Examples 1-5

[0039] The raw materials of Comparative Examples 1-3 are shown in Table 3 below, and the remaining ingredient is water.

[0040] Table 3 Raw materials of Comparative Examples 1-3

[0041] Examples 1-5 and Comparative Examples 1-3 provide a solid waste material-based microcrystalline foam ceramic material and a preparation method thereof, the raw materials are shown in Table 2 and Table 3, and the preparation method is as follows: (1) Put coal gangue, steel slag, glass powder and auxiliary ingredients into a ball mill and mix them evenly for 45 minutes.

[0042] (2) The mixed material obtained in step (2) is taken out from the ball mill in a vertical and uniform manner, and is placed in a corundum crucible with alumina coated around the bottom, and then placed in a high-temperature furnace for firing.

[0043] The firing method of step (2) is to increase the temperature to 1350°C at a heating rate of 15°C / min and keep the temperature for 40 min.

[0044] (3) After firing, immediately take out and place in cold water for water quenching to obtain quenched solid particles.

[0045] (4) The quenched solid particles obtained in step (3) are ball-milled for 40-50 min to obtain a 200-mesh powder material.

[0046] (5) The powdered material obtained in step (4) is mixed with the foaming component, the fluxing component and deionized water in a blender and evenly mixed. The slurry is poured into a mold, allowed to stand for 2 days, demolded, and then placed in an oven for drying for 24 hours until constant weight is obtained to obtain an embryo body.

[0047] (6) Place the embryo obtained in step (5) into a muffle furnace and fire it according to the following firing method: The firing method of step (6) is to first increase the temperature to 660°C at a heating rate of 5°C / min and keep it at that temperature for 45 min; then increase the temperature to 850°C at a heating rate of 6°C / min and keep it at that temperature for 60 min; then increase the temperature to 960°C at a heating rate of 6°C / min and keep it at that temperature for 60 min.

[0048] Finally, a solid waste material-based microcrystalline foam ceramic material is obtained. Example 6

[0049] The present embodiment provides a solid waste material-based microcrystalline foam ceramic material and a preparation method thereof. The raw materials are the same as those in Example 1. The preparation method is different from that in Example 1 in that: the firing method in step (6) is to first heat the temperature to 700°C at a heating rate of 8°C / min and keep the temperature for 45 min, then heat the temperature to 950°C at a heating rate of 7°C / min and keep the temperature for 60 min, then heat the temperature to 1060°C at a heating rate of 6°C / min and keep the temperature for 60 min. Example 7

[0050] The present embodiment provides a solid waste material-based microcrystalline foam ceramic material and a preparation method thereof. The raw materials are the same as those in Example 1, and the preparation method is different from that in Example 1 in that: the firing method in step (6) is to first heat the temperature to 900°C at a heating rate of 3°C / min and keep the temperature for 45 min, then heat the temperature to 950°C at a heating rate of 5°C / min and keep the temperature for 60 min, then heat the temperature to 1060°C at a heating rate of 5°C / min and keep the temperature for 60 min.

[0051] Comparative Example 4 This comparative example provides a solid waste material-based microcrystalline foam ceramic material and a preparation method thereof. The raw materials are the same as those in Example 1, and the preparation method is different from that in Example 1 in that: the firing method in step (6) is to heat the material to 750°C at a heating rate of 5°C / min and keep the temperature for 45 min, then heat the material to 960°C at a heating rate of 5°C / min and keep the temperature for 60 min.

[0052] Comparative Example 5

[0053] This comparative example provides a solid waste material-based microcrystalline foam ceramic material and a preparation method thereof. The raw materials are the same as those in Example 1, and the difference between the preparation method and Example 1 is that the firing method in step (6) is to heat the material to 850°C at a heating rate of 5°C / min and keep the temperature for 45 min, then heat the material to 1060°C at a heating rate of 10°C / min and keep the temperature for 60 min.

[0054] Comparative Example 6 This comparative example provides a solid waste material-based microcrystalline foam ceramic material and a preparation method thereof. The raw materials are the same as those in Example 1, and the preparation method is different from that in Example 1 in that the firing method in step (6) is to heat the material to 1060°C at a heating rate of 8°C / min and keep the temperature for 45 min.

[0055] Test example

[0056] The solid waste material-based microcrystalline foam ceramic materials prepared by Examples 1-7 and Comparative Examples 1-6 were subjected to performance tests, and the test results are shown in Table 4 below. As can be seen from Table 4, when the raw material does not contain auxiliary components, contains only one auxiliary component, and the embryo body firing method is different from the present invention, the porosity and compressive strength of the prepared solid waste material-based microcrystalline foam ceramic material are greatly reduced, and its water absorption rate is also affected to a certain extent. When the raw materials and preparation methods of the invention are used, the water absorption rate, porosity and compressive strength of the prepared solid waste material-based microcrystalline foam ceramic material are significantly better.

[0057] Table 4 Performance test results of solid waste-based microcrystalline foam ceramic materials

[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A solid waste material-based microcrystalline foam ceramic material, characterized in that: The raw materials include 15-32% coal gangue, 20-38% steel slag, 30-45% glass powder, 4-11% auxiliary components, 3-7% fluxing components, 4-7% foaming components, and 1-5% water by weight; the auxiliary components include TiO2 and ZrO2.

2. The solid waste material-based microcrystalline foam ceramic material according to claim 1, characterized in that: Among the auxiliary components, the weight ratio of TiO2 and ZrO2 is (1~5): (2~5).

3. The solid waste material-based microcrystalline foam ceramic material according to claim 2, characterized in that: Among the auxiliary components, the weight ratio of TiO2 and ZrO2 is 3:

2.

4. The solid waste material-based microcrystalline foam ceramic material according to claim 3, characterized in that: The raw materials include, by weight percentage, 16.79% coal gangue, 33.32% steel slag, 30.89% glass powder, 8% auxiliary components, 5% fluxing components, 5% foaming components, and 1% water.

5. The solid waste material-based microcrystalline foam ceramic material according to claim 1, characterized in that: The gangue and steel slag are obtained by removing impurities, crushing, grinding and screening the gangue raw materials and steel slag raw materials respectively, so as to obtain particles with a particle size not exceeding 0.075 mm.

6. The solid waste material-based microcrystalline foam ceramic material according to claim 1, characterized in that: The foaming components include SiC, MnO2, and CaCO3, and the weight ratio thereof is (2~5):(0.5~2):(0.5~2).

7. The solid waste material-based microcrystalline foam ceramic material according to claim 1, characterized in that: The fluxing component is borax or fluorite powder, and the weight ratio thereof is 5%.

8. The method for preparing a solid waste material-based microcrystalline foam ceramic material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) The coal gangue, steel slag, glass powder and auxiliary components are mixed uniformly, and then fired, water quenched and ground to obtain a powdered material; (2) uniformly mixing the powdered material, foaming component, fluxing component and water, pouring into a mold, letting it stand, demolding, and drying to obtain an embryo body; (3) The embryo body is first heated to 650-900°C at a heating rate of 3-8°C / min and kept warm for 30-50 min, then heated to 800-1000°C at a heating rate of 5-8°C / min and kept warm for 60-80 min, and finally heated to 950-1100°C at a heating rate of 3-8°C / min and kept warm for 60-80 min, to obtain the solid waste material-based microcrystalline foam ceramic material.

9. The method for preparing the solid waste material-based microcrystalline foam ceramic material according to claim 8, characterized in that: The firing method in step (1) is to increase the temperature to 1200°C~1350°C at a heating rate of 5~30°C / min and keep the temperature for 30~45min.

10. The method for preparing the solid waste material-based microcrystalline foam ceramic material according to claim 8, characterized in that: The particle size of the powdered material is 150 mesh to 250 mesh.

Citation Information

Patent Citations

  • Diopside-based microcrystalline ceramic and preparation method thereof

    CN116655248A

  • CaO-MgO-SiO2 system microcrystalline ceramic and preparation method thereof

    CN116969684A